LITERATUR STUDY OF UTILIZATION OF SOLAR CELLS FOR SUPPORTING AGRICULTURE (Teknosia, 2023)
Indonesia is known as a country whose economy depends on or is supported by the agricultural sector. But now climate change poses an increasingly greater threat. The agricultural sector is very vulnerable to climate change because of its dependence on weather. Renewable energy is expected to surpass the use of coal in electricity generation in the second half of the 2020s, and by 2050, renewable energy will account for 50% of global electricity generation. Based on the data, there is a lot of use of solar cells to support energy in the agricultural sector. There are several uses, such as irrigation, drying, spraying, fertilizing, pest control, and controlling pH and temperature. Apart from that, using solar panels also has the advantage of being environmentally friendly, economical, efficient, and can be used for a long period.